(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The article offers a theoretical contribution for reading women’s process of separation from the ’ndrangheta through an innovative approach. First, it highlights how the condition of vulnerability can represent a heuristic tool useful for taking the distance from the Mafia. Afterwards it wonders about the risks of paternalism inherent in interventions of support for these women, suggesting that they should be elaborated within the horizon of the care’s ethics and relational autonomy.